Computer security self-efficacy factors influencing e-banking utilization and user satisfaction - Al-Shawabkeh, Mahmoud; Mohd Saudi, Madihah; Moha Alwi, Najwa Hayaati (2012)
Given a paucity of research and apparent lack of coherence in information system research, it seems that there is no consensus in the information system field as to how security fits into the information system acceptance, usage, success, utilization, and/or performance impact (effectiveness, efficiency, and satisfaction). This study designed as a part of ongoing research aims to extend the Technology-to-Performance Chain (TPC) model by including the Computer Security Self-Efficacy (CSSE) construct, a strategy of model extension suggested by several researchers. The primary purposes of the study are to establish the reliability of the scales and to gain a preliminary understanding of the model fit. This study determined the computer security factors that affecting the E-Banking utilization and user satisfaction. An investigation and analysis were made to identify whether user self-efficacy such as computer self-efficacy (CSE), Internet self-efficacy (ISE), and computer security self-efficacy (CSSE) has relationship towards the e-banking utilization and user satisfaction.